(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were to study analytical thinking ability on mathematics, to compare analytical thinking ability on mathematics with the criteria, and to study collaboration, teamwork and leadership after using Learning and Enjoying Model with Mind Mapping. The samples were pre-service teachers in Mathematics program. The instrument consists of the process of Learning and Enjoying Model with Mind Mapping, the test about analytical thinking ability on mathematics, and the collaboration, teamwork and leadership questionnaire. Data analyzed by percentage, mean, standard deviation, and t-test one group. The results found that, pre-service teachers had 74.64 percent of analytical thinking ability on mathematics and it was higher than the criteria of 70 percent at .05 level of significance, when considered in each aspect found that the analysis of element had highest percent, then the analysis of relationship, and analysis of organizational principles respectively. Moreover, pre-service teachers had collaboration, teamwork and leadership as a whole at a high level. Considering that everyone willing to accept the results of their work in highest average, followed by every member is important for work success according to goal, they believe that every members of the group can work towards their goals, and all members are involved in decision-making respectively. Pre-service teachers commented, this learning process has easy steps to implement with students. Creating a Mind Mapping is connecting a content to help understand the details and whole of the contents